(untitled) (Sains Humanika, 2023)
In comparison to developed nations, the utilisation of e-learning in developing countries remains relatively uncommon. Consequently, this research addresses the prevailing call in the academic literature for increased investigation into the reception, integration, and utilisation of e-learning systems and applications among English-language educators in Libyan universities, aiming to contribute to the existing knowledge gap. This study conducted a systematic literature review (SLR) following the PRISMA 2020 guidelines. This rigorous method centred on theories and models related to the acceptance of e-learning technology, the pertinent issues and challenges encountered within Libyan higher education institutions. The findings of the PRISMA-guided review shown that Technological Acceptance Model (TAM) stands as the predominant theoretical framework employed to assess the adoption of e-learning in Libyan universities. Conversely, studies grounded in alternative technological acceptance theories, such as the Unified Theory of Acceptance and Use of Technology (UTAUT) and Theory of Reasoned Action (TRA), are notably scarce. Therefore, this study advocates for the continued utilisation of the TAM framework in forthcoming research endeavours due to its comprehensive foundation in technology acceptance models and its capacity to offer novel insights. The results of this PRISMA-guided study hold potential significance for scholars engaged in the examination of technology adoption for teaching and learning the English language as a foreign language (EFL), particularly in the context of developing countries.